A single enhancer regulating the differential expression of duplicated red-sensitive opsin genes in zebrafish. - Taro Tsujimura; Tomohiro Hosoya; Shoji Kawamura (PLoS Genetics, 2010)
A fundamental step in the evolution of the visual system is the gene duplication of visual opsins and differentiation between the duplicates in absorption spectra and expression pattern in the retina. However, our understanding of the mechanism of expression differentiation is far behind that of spectral tuning of opsins. Zebrafish (Danio rerio) have two red-sensitive cone opsin genes, LWS-1 and LWS-2. These genes are arrayed in a tail-to-head manner, in this order, and are both expressed in the long member of double cones (LDCs) in the retina. Expression of the longer-wave sensitive LWS-1 occurs later in development and is thus confined to the peripheral, especially ventral-nasal region of the adult retina, whereas expression of LWS-2 occurs earlier and is confined to the central region of the adult retina, shifted slightly to the dorsal-temporal region. In this study, we employed a transgenic reporter assay using fluorescent proteins and P1-artificial chromosome (PAC) clones encompassing the two genes and identified a 0.6-kb "LWS-activating region" (LAR) upstream of LWS-1, which regulates expression of both genes. Under the 2.6-kb flanking upstream region containing the LAR, the expression pattern of LWS-1 was recapitulated by the fluorescent reporter. On the other hand, when LAR was directly conjugated to the LWS-2 upstream region, the reporter was expressed in the LDCs but also across the entire outer nuclear layer. Deletion of LAR from the PAC clones drastically lowered the reporter expression of the two genes. These results suggest that LAR regulates both LWS-1 and LWS-2 by enhancing their expression and that interaction of LAR with the promoters is competitive between the two genes in a developmentally restricted manner. Sharing a regulatory region between duplicated genes could be a general way to facilitate the expression differentiation in duplicated visual opsins.